Enzyme replacement in Fabry disease: pharmacokinetics and pharmacodynamics of agalsidase alfa in children and adolescents - Ries, Markus (Journal of clinical pharmacology, 2007)
This multicenter, open-label study evaluated pharmacokinetics, pharmacodynamics, and safety of agalsidase alfa in pediatric compared with adult patients with Fabry disease. The pharmacokinetic parameters of pediatric patients (19 boys, 5 girls, 6-18 years old; mean age, 11.8 years) were compared to those of adult male and female patients who participated in other clinical studies. All patients received agalsidase alfa at a dose of 0.2 mg/kg infused over 40 minutes every other week. Agalsidase alfa exhibited a biphasic serum elimination profile with a maximum serum concentration at the end of the 40-minute infusion; <1% of the maximum concentration was detected 8 hours after dosing. In children, serum clearance was 2.0 to 9.4 mL/min/kg and tended to decrease with increasing age. The average clearance in children, 3.7 ± 1.5 mL/min/kg (mean ± SD), was significantly greater than that measured in 33 adults (2.3 ± 0.7 mL/min/kg1 P < .0001). Mean terminal elimination half-life of agalsidase alfa was prolonged in week 25 compared with baseline (150 vs 66 minutes) in 8 of 19 male children. The magnitude of the reduction of plasma globotriaosylceremide was similar in all age groups and was independent of area under the curve and other pharmacokinetic parameters. Except for clearance in younger patients, agalsidase alfa appears to have comparable pharmacokinetic and pharmacodynamic profiles in pediatric and adult Fabry patients of both genders.
First published: 07 March 2013
Gesehen am 09.05.2019